Characterization of active layer thickening rate over the northern Qinghai-Tibetan Plateau permafrost region using alos interferometric synthetic aperture radar data, 2007-2009 - Jia, Y; Kim, JW; Shum, C; Lu, Z; Ding, XL; Zhang, L; Erkan, K; Kuo, CY; Shang, K; Tseng, KH; Yi, Y (Remote Sensing, 2017)
2016-2017 > Academic research: refereed > Publication in refereed journal 201804_a bcma Version of Record Published